Identification of Novel Conjugative Plasmids with Multiple Copies of fosB that Confer High-Level Fosfomycin Resistance to Vancomycin-Resistant Enterococci - Sun, Lingyan; Zhang, Ping; Qu, Tingting; Chen, Yan; Hua, Xiaoting; Shi, Keren; Yu, Yunsong (Frontiers in Microbiology, 2017)
To further characterize the fosB-carrying plasmids of 19 vancomycin-resistant enterococci, the complete sequences of the fosB- and vanA-containing plasmids of E. faecium (pEMA120) and E. avium (pEA19081) were obtained by single-molecule, real-time sequencing. We found that these two plasmids are essentially identical (99.99% nucleotide sequence identity), which proved the possibility of interspecies transmission. Comparative analysis of the plasmids revealed that the backbone of pEMA120 is 99% similar to a conjugative fosB-negative E. faecium plasmid, pZB18. There is a traE disrupted in the transfer region of pEMA120, in comparison to pZB18 with an intact traE. The difference of their transfer frequencies between pEMA120 and pZB18 suggests this interruption of traE might affect conjugative transfer. Two copies of the fosB gene linked to a tnpA gene, forming an ISL3-like transposon, were found at separate locations within pEMA120, which had not been reported previously. These two fosB-carrying transposons were confirmed to form circular intermediates by inverse PCR. The hybridization of plasmid DNA digested by BsaI, having restriction site within the fosB sequence, demonstrated that the presence of multiple copies of fosB per plasmid is common. The total copy number of the fosB gene as revealed by qRT-PCR did not correlate with fosfomycin MICs or growth rates at sub-MICs of fosfomycin in different transconjugants. From susceptibility tests, the fosB gene, regardless of the copy number, conferred high fosfomycin MICs that ranged from 16384 to 65536 μg/ml. This first complete nucleotide sequence of a plasmid carrying two copies of fosB in VRE suggests that the fosB gene can transfer to multiple loci of plasmids by the ISL3 family transposase TnpA, possibly in the form of circular intermediates, leading to the dissemination of high fosfomycin resistance in VRE.